Peningkatan Keterampilan Produktif Calon Guru SMK Otomotif melalui Kemitraan dengan Industri - Gunadi, Gunadi (Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
LPTK as the Teacher Education Institution currently experiences increasing challenges in rising more professional candidates and the goverment policy of the teacher recruitment process. The teachers candidates experience limited learning facilities, and it influences their competencies as teachers in Vocational High Schools. The students as the teacher candidates who lack of experiences in industrial environment will have low motivation and passion in the real working world. Therefore, LPTK needs to establish partnerships with schools and industries. Some of the partnerships that are potential to be developed by LPTK includes vocational laboratory simulations, apprenticeships, internships, school-based enterprises, cooperative education, and job shadowing. The hard skills (job skills, teaching skills productive) and the soft skills (attitudes, characters and work climate) are expected to be developed therefore the knowledge and the experiences will be transferred to the students in Vocational High Schools